2016
DOI: 10.1093/jxb/erw115
|View full text |Cite
|
Sign up to set email alerts
|

Root hair formation in rice (Oryza sativaL.) differs between root types and is altered in artificial growth conditions

Abstract: Root hairs are important sites for nutrient uptake, especially in P limiting conditions. Here we provide first insights into root hair development for the diverse root types of rice grown under different conditions, and show the first in situ images of rice root hairs in intact soil. Roots of plants grown in upland fields produced short root hairs that showed little responsiveness to P deficiency, and had a higher root hair density in the high P condition. These results were reproducible in rhizoboxes under gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 38 publications
8
93
0
Order By: Relevance
“…Another possibility is that, as a cell that extends from the plant body into the rhizosphere, the root hair may evolve and utilize multiple developmental strategies to effectively interact with and adapt to a varying environment. In support of this, root hair growth in many species is known to be strongly influenced by nutrient availability (Perry et al, 2007;Nestler et al, 2016;Salazar-Henao et al, 2016). Alternatively, the strong selection for high yield imposed on most of these species during their domestication may be responsible for the high degree of root hair gene divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that, as a cell that extends from the plant body into the rhizosphere, the root hair may evolve and utilize multiple developmental strategies to effectively interact with and adapt to a varying environment. In support of this, root hair growth in many species is known to be strongly influenced by nutrient availability (Perry et al, 2007;Nestler et al, 2016;Salazar-Henao et al, 2016). Alternatively, the strong selection for high yield imposed on most of these species during their domestication may be responsible for the high degree of root hair gene divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Field sites are located in Tsukuba, Japan, and soil properties have been described elsewhere (Nestler et al, 2016). The same P deficient Andosol soil from the upland field plot was used to fill Rhizoboxes.…”
Section: Methodsmentioning
confidence: 99%
“…Although P deficiency can lead to increased root hair length and density in tomato ( Lycopersicon esculentum ), rape ( Brassica oleracea ), spinach ( Spinacia oleracea ) (Foehse and Jungk, 1983), common bean ( Phaseolus vulgaris , Miguel et al, 2015), and Arabidopsis thaliana (Bates and Lynch, 1996) this is not a general observation for plant species or even among varieties of a species. Recently, it was demonstrated that P deficient soil can even lead to formation of shorter root hairs on rice ( Oryza sativa ) roots compared to sufficiently P supplied soil (Nestler et al, 2016). And among 166 Arabidopsis genotypes the majority showed no difference in root hair length in relation to P level (Stetter et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…type C roots) with xylem differentiated down to the tip are suspected to facilitate water uptake Wang et al, 1994). In rice, the presence of short, thin, and abundant lateral roots has been interpreted functionally as super root hairs (Nestler et al, 2016), increasing the root surface area and nutrient uptake, in particular for immobile ions such as phosphorus, while at the same time having a low carbon cost as compared with long lateral roots. By contrast, long lateral roots (i.e.…”
Section: Which Role For the Three Lateral Root Types?mentioning
confidence: 99%